PKM TRAINING-INTRODUCTION TO ENGLISH VOCABULARY VIA FLASHCARD FOR TEACHERS RA NURUSSA'ADAH - Nurul frijuniarsi; Natalia Tri Astuti; Zumrotul Muniroh (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
Teaching to kindergarten must be concrete, this is because at that age children do not have sufficient ability to absorb abstract things. A clear explanation is needed in introducing a new knowledge to children. In addition, in the process of learning activities must be interesting and stimulate their sensory. Vocabulary recognition in a foreign language, in this case English, can be done by taking into these two principles, therefore, flashcard-assisted learning can be used as an alternative, because flashcards have interesting pictures and can be customized. with the needs of the teacher in his goal of teaching English vocabulary.